2009
DOI: 10.1063/1.3182806
|View full text |Cite
|
Sign up to set email alerts
|

Thermal lens measurement of the Soret coefficient in acetone/water mixtures

Abstract: The Soret coefficient of acetone/water mixtures has been experimentally determined by a recently developed thermal lens technique ͓Appl. Phys. Lett. 94, 051103 ͑2009͔͒. The behavior of the Soret coefficient was reproduced, including its sign change with composition. For concentrations around the equimolar ones, we have also confirmed the disagreement between the experimental and simulation data that had previously been reported by Ning and Wiegand ͓J. Chem. Phys. 125, 221102 ͑2006͔͒ using a transient holograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The TL setup has been recently used to study binary liquid mixtures of water and acetone [127,128]. Polyakov and Wiegand demonstrated that the TL apparatus is suitable to investigate the Soret effect in aqueous as well as non-aqueous liquid mixtures [122].…”
Section: Thermal Lens Methodsmentioning
confidence: 99%
“…The TL setup has been recently used to study binary liquid mixtures of water and acetone [127,128]. Polyakov and Wiegand demonstrated that the TL apparatus is suitable to investigate the Soret effect in aqueous as well as non-aqueous liquid mixtures [122].…”
Section: Thermal Lens Methodsmentioning
confidence: 99%
“…On the other hand, the intermolecular interactions contribute differently in different binary samples in the measurement of the TL signal. Intermolecular interactions and the change in bonding situations that result from the molecular properties generally depend on various parameters like the inter-and intramolecular bonding nature of individual binary components, molecular diffusion under steady state condition (Sorret effect) 26,34 of the binary solutions, critical time constants of the solutions, etc. Thus, the contribution originating from the change in the molecular properties of the binary mixture results in the observed difference between experimental and calculated trends of the thermal-lens signal across the change of the composition of the binary solutions under the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the beam deflection technique, the Soret cell has transparent walls and evolution of composition is observed via deflection of a laser beam passing through the medium. 19,20 In the thermal lens technique, 21,22 the temperature gradient is created by heat generation resulting from the absorption of light into the fluid. The sample behaves like an optical lens due to the change of refractive index resulting from thermal and compositional gradients.…”
Section: Introductionmentioning
confidence: 99%